Application of Problem Based Learning (PBL) Learning Model to Improve Students' Learning Outcomes and Interest in Thermochemistry Material at SMA Muhammadiyah 2 Medan - Elvi Zurryyati Pratama; Nora Susanti; Rizki Kholilah Lubis (Jurnal Pendidikan dan Pembelajaran Kimia, 2025)
Application of Problem Based Learning (PBL) Learning Model to Improve Students' Learning Outcomes and Interest in Thermochemistry Material at SMA Muhammadiyah 2 Medan. This study aims to determine whether there is an influence on learning outcomes by applying the PBL learning model to thermochemistry material at SMAS Muhammadiyah 2 Medan. To find out how the interest in applying the PBL learning model to thermochemistry material at SMAS Muhammadiyah 2 Medan. This research was conducted at SMAS Muhammadiyah 2 Medan in September - February of the 2024/2025 academic year. The research method used was a quasi-experimental design with a non-equivalent control group design. The research sample consisted of class XI-R1 as the control class and XI-R2 as the experimental class selected by purposive sampling. Hypothesis I testing was carried out using the Independent Sample T-Test, with the results of the study showing a sig value of 0.007 <0.05 which means that the hypothesis (Ha) is accepted and (H0) is rejected. Hypothesis II testing was conducted using the Independent Sample T-Test, with the results showing a sig value of 0.012 <0.05, which indicates that there is a positive student response to the (PBL) learning model on thermochemistry material on student learning interest, which means that the Hypothesis (Ha) is accepted.